Effects of cilengitide derivatives on TGF-β1-induced epithelial-to-mesenchymal transition and invasion in gefitinib-resistant non-small cell lung cancer cells - Seo, Yujin; Seo, Minji; Kim, Jiyeon (Frontiers in Pharmacology, 2023)
Long-term administration of tyrosine kinase inhibitors (TKIs) used for the treatment of nonsmall cell lung cancer (NSCLC) induces TKI resistance in cells. The appearance of resistant cells requires the combined administration of another therapeutic agent and may cause side effects in the gastrointestinal and central nervous system. In previous studies, we found that derivatives of cilengitide, a cyclic Arg-Gly-Asp (RGD) peptide, exert NSCLC apoptotic and anti-epithelial-mesenchymal transition (EMT) effects. In particular, cRGDwV and cRGDyV, which are cyclic peptides containing aromatic amino acids, were found to inhibit NSCLC cell growth, TGF-β1-induced EMT, and invasion. In this study, we confirmed the effects of cRGDwV and cRGDyV on proliferation, TGF-β1-induced EMT marker expression, migration, and invasion in gefitinib-resistant NSCLC A549 (A549GR) cells. In A549GR cells, cRGDwV and cRGDyV showed inhibitory effects on the expression of mesenchymal marker expression, migration, and invasion. These results indicate that cyclic RGD peptides containing aromatic amino acids can be used to inhibit mesenchymal marker expression as well as migration and invasion in gefitinib-resistant cells.